Catalogue of non-marine Polychaeta (Annelida) of the World - Glasby, Christopher J.; Timm, Tarmo; Muir, Alexander I.; Gil, João (Zootaxa, 2009)
An annotated checklist and bibliography of 197 species (representing 78 genera and 26 families) of non-marine polychaetes of the world is presented, including synonymies, information on ecology, distribution, habitat, and references to the taxonomic and biological literature. Over half (57%) of the checklist species are represented by just three families as follows: Nereididae (61 species including Namanereis, Namalycastis, Neanthes and Hediste), Aeolosomatidae (27 species, mostly Aeolosoma) and Sabellidae (24 species including Caobangia and Manayunkia). Other well-represented taxa are the epizoic histriobdellid Stratiodrilus (11 species), the inland-sea-specialist ampharetid Hypania and related genera (5 species), and the freshwater-tolerant spionid Marenzelleria (5 species). One new combination is proposed for the nereidid Nereis tenuipalpa Pflugfelder, 1933, viz. Paraleonnates tenuipalpa n. comb.